Formation of the Management Information System in the Education Sector and the Development of the Education System of the Republic of Belarus Based on the Experience of Estonia - P. A. Lis; D. A. Kachan; V. I. Slizh; A. B. Belsky (Цифровая трансформация)
The article considers the issues of formation and maintenance of an integrated information management system in the education sector, as well as the development of e-education on the example of the Republic of Estonia — a regional and one of the world leaders in the field of digital transformation of education. The history and specificity of the information system in the Estonian education sector (EHIS) is analyzed in the context of the development of e-government technologies. The principles for the processes of collecting, processing and analyzing information in the education sector in Estoniaare presented, the expanded analytical capabilities of the information system containing personal data of various categories of participants in the educational process are described. The issues of ensuring confidentiality and integrity of information based on digital signature and blockchain technology are considered. The economic and social effect of the implementation of an integrated information system in the education sector has been revealed. The structure of e-learning services in Estoniaand their role in providing digital transformation of the education system are considered. As a result of the analysis of the Estonian experience in the formation of an integrated information system in the education sector, as well as the development of e-education services, scientifically based recommendations for the modernization of the education system of the Republicof Belarushave been developed.